Hair and Scalp Disorders 2017
DOI: 10.5772/66747
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Procedures in the Treatment of Alopecia

Abstract: Alopecia has a significant negative impact on the quality of life. Unfortunately, there is no satisfactory cure for most types of alopecia. Alopecia is divided into cicatricial and noncicatricial types. Androgenetic alopecia, alopecia areata, and telogen effluvium are common forms of noncicatricial alopecias. In order to treat or improve the appearance, various procedures that are being applied for different types of alopecia including mesotherapy, microneedling, platelet-rich plasma, low-level light therapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 116 publications
(192 reference statements)
1
1
0
Order By: Relevance
“…Trichoscopic findings at the beginning and conclusion of the sixth month were significantly different in the Botox group ( p = 0.01), while this difference was extremely significant in the LC group ( p = 0.009). This coincides with Kartal et al 11 His study was on 30 patients with AGA; they studied 15 people given 5% Capixyl lotion and 15 people given a placebo for 4 months and discovered that Capixyl increased anagen hair density while reducing telogen density more than the placebo. This was explained by Talavera‐Adame et al 12 as they suggested that a direct action of Capixyl on 5‐a‐reductase helps prevent hair shrinkage by modulating dihydrotestosterone.…”
Section: Discussionsupporting
confidence: 80%
“…Trichoscopic findings at the beginning and conclusion of the sixth month were significantly different in the Botox group ( p = 0.01), while this difference was extremely significant in the LC group ( p = 0.009). This coincides with Kartal et al 11 His study was on 30 patients with AGA; they studied 15 people given 5% Capixyl lotion and 15 people given a placebo for 4 months and discovered that Capixyl increased anagen hair density while reducing telogen density more than the placebo. This was explained by Talavera‐Adame et al 12 as they suggested that a direct action of Capixyl on 5‐a‐reductase helps prevent hair shrinkage by modulating dihydrotestosterone.…”
Section: Discussionsupporting
confidence: 80%
“…Hyperkeratosis (scaling), pruritus, alopecia (hair loss) and inflammatory signs (erythema) are common symptoms of scalp disorders often related to a greater susceptibility of the scalp to bacterial or mycotic infections [28]. Scalp microbiome analyses showed that the most abundant bacteria found in the scalp are C. acnes, S. aureus and S. epidermidis; M. furfur is among the most common cutaneous commensal fungi of the scalp [29,30]. On undamaged skin, this resident microbiome provides a benefit to skin integrity and is considered non-pathological.…”
Section: Discussionmentioning
confidence: 99%